FOUCAULT. AN AESTHETIC OF EXISTENCE - Rodríguez, Joe Stivens (Disertaciones, 2017)
In this article, the reader will find a possible link between work and existence in M. Focault. How his philosophical work can shape his own life; how the research itinerary, from the direct contact with its research problems, its problematization and its historical display, carried out based on perspectivistic hermeneutics, creates the transvaluation of him.
Keywords: critical attitude; ethics; aesthetic; perspectivism